ChemInform Abstract: Palladium‐Catalyzed Aerobic Oxidative C—H Olefination with Removable 1, 2, 3‐Triazole Directing Group. Issue 10 (March 2015) - Ye, Xiaohan; Shi, Xiaodong
Abstract The selectivity of mono‐ and diolefination is poor in case of substrates (I).